2022
DOI: 10.3390/earth3020038
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Environmental Implications of Bioenergy Crop Cultivation on Marginal African Drylands and Key Principles for a Sustainable Development

Abstract: Africa has been a hotspot for the development of food and bioenergy crop cultivation since the 2000s, leading to systematic challenges towards its ability to become a bioeconomy. To reduce land-use conflicts with food crop cultivation, marginal African drylands (MADs) are proposed for sustainable bioenergy cropping systems (BCSs). This study reviews the foremost socio-economic and environmental challenges for BCSs on MADs, and the development of key principles for minimizing adverse outcomes towards a sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…A better understanding of ecosystem services provided by MAL would also result from a thorough evaluation of biodiversity. A comprehensive understanding of the MAL requires an understanding of their ability to provision ecosystem services and their socio-economic situations [33,113,206,207]. The diversification of agroecosystems at landscape level through a purposeful implementation of perennial biomass crops with different growth cycles could increase the agroecosystems' resilience-especially in the face of increasing climate change impacts [42].…”
Section: Benefits and Limitations Of Biodiversity Evaluation On Margi...mentioning
confidence: 99%
“…A better understanding of ecosystem services provided by MAL would also result from a thorough evaluation of biodiversity. A comprehensive understanding of the MAL requires an understanding of their ability to provision ecosystem services and their socio-economic situations [33,113,206,207]. The diversification of agroecosystems at landscape level through a purposeful implementation of perennial biomass crops with different growth cycles could increase the agroecosystems' resilience-especially in the face of increasing climate change impacts [42].…”
Section: Benefits and Limitations Of Biodiversity Evaluation On Margi...mentioning
confidence: 99%
“…As populations increase and agriculture intensifies, eutrophication of freshwater bodies around the globe, particularly in Africa, is becoming a major challenge [1]. Water quality monitoring is essential to identify water contamination sources and implement best management practices for healthy ecosystems [2].…”
Section: Introductionmentioning
confidence: 99%
“…Another optical property of water, TUR, scatters and absorbs light rather than transmitting it. Total dissolved and suspended solids are responsible for most of the scattering, whereas absorption is controlled by Chl-a and colored dissolved or particulate matter [1]. TUR and total suspended solids are important variables in many studies due to their linkage with incoming sunlight, affecting photosynthesis for the growth of algae and plankton in water bodies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, by explicitly including in our analysis the role of women and gender equality, we aimed to highlight the fundamental contribution of these drivers to the consolidation of the bioeconomy and its further development. To date, a very limited number of studies have revealed the nexus between the role of women and gender equality and the bioeconomy progress (see, e.g., [ 21 , 22 ]). However, none of these studies emphasized the importance of women and gender equality in creating added value in the bioeconomy sphere.…”
Section: Introductionmentioning
confidence: 99%